Facial Expression Processing Across the Autism–Psychosis Spectra: A Review of Neural Findings and Associations With Adverse Childhood Events - Samaey, Celine; Van der Donck, Stephanie; van Winkel, Ruud; Boets, Bart (Frontiers in Psychiatry, 2020)
Autism spectrum disorder (ASD) and primary psychosis are classified as distinct neurodevelopmental disorders, yet they display overlapping epidemiological, environmental and genetic components as well as (endo)phenotypic similarities. For instance, both disorders are characterized by impairments in facial expression processing, a crucial skill for effective social communication, and both disorders display an increased prevalence of adverse childhood events (ACE). This narrative review provides a brief summary of findings from neuroimaging studies investigating facial expression processing in ASD and primary psychosis with a focus on the commonalities and differences between these disorders. Individuals with ASD and primary psychosis activate the same brain regions as healthy controls during facial expression processing, albeit to different extent. Overall, both groups display altered activation in the fusiform gyrus and amygdala as well as altered connectivity among the broader face processing network, probably indicating reduced facial expression processing abilities. Furthermore, delayed or reduced N170 responses have been reported in ASD and primary psychosis, but the significance of these findings is questioned, and alternative frequency-tagging EEG measures are currently explored to capture facial expression processing impairments more selectively. Face perception is an innate process, but is also guided by visual learning and social experiences. Extreme environmental factors, such as adverse childhood events (ACE), can disrupt normative development and alter facial expression processing. ACE is hypothesized to induce altered neural facial expression processing, in particular a hyperactive amygdala response towards negative expressions. Future studies should account for the comorbidity among ASD, primary psychosis and ACE when assessing facial expression processing in these clinical groups, as it may explain some of the inconsistencies and confounds reported in the field.